THE INFLUENCE OF STORE ATMOSPHERE AND LIFESTYLE ON IMPULSE BUYING AT MINISO MALL OLYMPIC GARDEN KOTA MALANG - Syahputri, Wineke Ardhila; Budiarti, Lina (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Impulse buying behavior is described as an unplanned purchase that is made spontaneously, followed by conflicting thoughts and emotional impulses. The impulse buying phenomenon can be an opportunity for retailers to increase sales turnover and a challenge to create an attraction for consumers to visit outlets and make purchases. Consumer impulse buying behavior can be influenced by several things, namely store atmosphere and lifestyle. Research Purpose. To analyze the influence of store atmosphere and lifestyle on impulse buying at Miniso Mall Olympic Garden, Malang City. Research Method. This research was a quantitative research with store atmosphere, lifestyle, and impulse buying variables. Data of the research was collected through a questionnaire and with a saturated sampling technique, 160 respondents were obtained who were students of the D-IV Marketing Management study program. Data analysis in this research was used multiple linear regression analysis. Findings. The store atmosphere variable has a t-count of 2.215 > t-table 1.975 and with a significance of 0.028 < 0.05. The lifestyle variable has a t-count of 7.964 > t-table 1.975 and with a significance of 0.000 < 0.05. The store atmosphere and lifestyle variables have an F-value of 66.280 > f-table 3.05 and with a significance value of 0.000 < 0.05. Conclusion. The research results showed that partially and simultaneously store atmosphere and lifestyle has a positive and significant effect on impulse buying. In this research, lifestyle variables were found to have a bigger contribution than store atmosphere.